THE EFFECT OF ANTIOXIDANT ACTIVITY OF PLANTS TRIFOLIUM PRATENSE L. AND CRATAEGUS LAEVIGATA ON LIPID PEROXIDATION IN RAT'S TISSUES EXPOSED TO HYPOBARIC HYPOXIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The processes of lipid peroxidation (LPO) were studied in rat brain and liver tissues under normal conditions, as well as under conditions of hypobaric hypoxia, since it is known that hypoxia causes the development of LPO in the cells of organism tissues. It has been also studied the influense of dry flowers of Trifolium pratense L. (red clover) and Crataegus laevigata (midland hawthorn) on lipid peroxidation, which triggers by hypobaric hypoxia. It has been shown, that the end product of lipid peroxidation malondialdehyde in rat brain and liver tissues was significantly decreased with the addition of plants flowers to the diet of animals, especially in the case of C. laevigata.
Keywords: hypobaric hypoxia; lipid peroxidation; Trifolium pratense L.; Crataegus laevigata